2012
DOI: 10.1093/deafed/ens043
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Aspects of Creativity in Deaf and Hearing High School Students

Abstract: To address the paucity of current research on the development of creativity in deaf students, and to extend existing research to adolescents, the present study investigated divergent thinking, a method of assessing creativity, in both deaf and hearing adolescents. We assessed divergent thinking in two domains, figural and verbal, while also adjusting the instructional method in written format, sign language, or spoken English. Deaf students' performance was equal to, or more creative than, hearing students on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…Research by foreign psychologists demonstrates trends consistent with our findings: children with hearing impairment are creative when solving creative tasks that do not involve the use of verbal speech [16]. They find unusual and original solutions in different spheres -in visual activities involving the use of images, in solving problems requiring the use of non-verbal means, in the production of gestures [18]. Specific features in the manifestation of creativity of hearing-impaired children are associated with the peculiarities of the cognitive sphere -the delay in the development of perception, memory, thought operations, and combinatorial abilities [19].…”
Section: Discussionsupporting
confidence: 85%
“…Research by foreign psychologists demonstrates trends consistent with our findings: children with hearing impairment are creative when solving creative tasks that do not involve the use of verbal speech [16]. They find unusual and original solutions in different spheres -in visual activities involving the use of images, in solving problems requiring the use of non-verbal means, in the production of gestures [18]. Specific features in the manifestation of creativity of hearing-impaired children are associated with the peculiarities of the cognitive sphere -the delay in the development of perception, memory, thought operations, and combinatorial abilities [19].…”
Section: Discussionsupporting
confidence: 85%
“…The data also revealed that deaf children had significantly higher scores on fantasy orientation than both blind and typically developing children, although the three groups did not differ on pretend play. Other studies have reported that deaf children had higher scores on measures of figural creativity than hearing children (Stanzione, Perez, & Lederberg, 2013) and, given that creativity and having an IC are strongly associated (Hoff, 2005; Singer & Singer, 1990), it may be that we have underestimated the role of fantasy and ICs in deaf children’s lives.…”
Section: Discussionmentioning
confidence: 89%
“…The data also revealed that deaf children had significantly higher scores on fantasy orientation than both blind and typically developing children, although the three groups did not differ on pretend play. Other studies have reported that deaf children had higher scores on measures of figural creativity than hearing children (Stanzione, Perez, & Lederberg, 2013) and, given that creativity and having an IC are strongly associated (Hoff, 2005;Singer & Singer, 1990), it may be that we have underestimated the role of fantasy and ICs in deaf children's lives. While the data from this study do not allow for developing causal models, there are several research trends related to Theory of Mind that may provide clues about why older deaf children appear to have above average rates of ICs and blind children appear to have lower than average rates of ICs.…”
Section: Imaginative Lives Of Deaf Blind and Typically Developing Cmentioning
confidence: 93%
“…Wang () has detailed the cognitive processes associated within creativity. Success with creativity correlates to success in reading, writing and mathematics (Jeon, Moon, & French, ; Stanzione, Perez, & Lederberg, ; Wang, ). Stanzione et al () advocate for additional research into creativity in students who are DHH.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Success with creativity correlates to success in reading, writing and mathematics (Jeon, Moon, & French, ; Stanzione, Perez, & Lederberg, ; Wang, ). Stanzione et al () advocate for additional research into creativity in students who are DHH. They believe that paper‐based assessments in creativity do not accurately reflect the creative competencies of a student who is DHH.…”
Section: Review Of Literaturementioning
confidence: 99%